Type and effectiveness of community-based interventions in improving knowledge related to cardiovascular diseases and risk factors: A systematic review - Hamid Yimam Hassen; Rawlance Ndejjo; Jean-Pierre Van Geertruyden; Geofrey Musinguzi; Steven Abrams; Hilde Bastiaens (American Journal of Preventive Cardiology, 2022)
Background: Despite an improvement in the healthcare system, cardiovascular diseases (CVDs) remain the leading cause of morbidity and mortality worldwide. Improving knowledge is a key for behavioral change towards prevention of CVDs. However, up-to-date evidence is limited on the effect of interventions on CVD knowledge. Thus this study aimed to synthesize comprehensive evidence on the type and effectiveness of community-based interventions (CBIs) to improve knowledge related to CVDs. Methods: We performed a systematic review of studies that tested the effectiveness of CBIs in improving CVD knowledge. International databases including MEDLINE, EMBASE, CINAHL, PSYCINFO and Cochrane register of controlled studies were searched for studies published between January 2000 and December 2019. The Cochrane risk of bias tools were used to assess the methodological quality of included studies. Since CVD knowledge was measured using various tools, results were synthesized narratively and reported in line with the reporting guideline for Synthesis Without Meta-analysis (SWiM). The review protocol is registered in the PROSPERO database (CRD42019119885). Results: 7 randomized and 9 non-randomized controlled trials involving 34,845 participants were included. Most of the interventions targeted the general population and majorities delivered the intervention to groups of individuals. Likewise, most of the interventions employed various intervention components including health education using different strategies. Overall, most studies showed that CBIs significantly improved knowledge related to CVDs. Conclusion: Community-based CVD preventive interventions are effective in improving knowledge related to CVD and risk factors. Measures to scale up CBIs are recommended to improve an individual's level of CVD knowledge, which potentially helps to counter the growing burden of CVDs.